Mitochondrial DNA and Functional Investigations into the Radiosensitivity of Four Mouse Strains - Zhang, Steven B. (Hindawi Publishing Corporation, 2014)
We investigated whether genetic radiosensitivity-related changes in mtDNA/nDNA ratios are significant to mitochondrial function and if a material effect on mtDNA content and function exists. BALB/c (radiosensitive), C57BL/6 (radioresistant), and F1 hybrid mouse strains were exposed to total body irradiation. Hepatic genomic DNA was extracted, and mitochondria were isolated. Mitochondrial oxygen consumption, ROS, and calcium-induced mitochondrial swelling were measured. Radiation influenced strain-specific survival in vivo. F1 hybrid survival was influenced by maternal input. Changes in mitochondrial content corresponded to survival in vivo among the 4 strains. Calcium-induced mitochondrial swelling was strain dependent. Isolated mitochondria from BALB/c mice were significantly more sensitive to calcium overload than mitochondria from C57BL/6 mice. Maternal input partially influenced the recovery effect of radiation on calcium-induced mitochondrial swelling in F1 hybrids; the hybrid with a radiosensitive maternal lineage exhibited a lower rate of recovery. Hybrids had a survival rate that was biased toward maternal input. mtDNA content and mitochondrial permeability transition pores (MPTP) measured in these strains before irradiation reflected a dominant input from the parent. After irradiation, the MPTP opened sooner in radiosensitive and hybrid strains, likely triggering intrinsic apoptotic pathways. These findings have important implications for translation into predictors of radiation sensitivity/resistance.